PENDIDIKAN KESEHATAN BERPENGARUH TERHADAP TINGKAT PENGETAHUAN KLIEN TENTANG PERAWATAN PASCA OPERASI KANKER PAYUDARA - Siwu, Lusi; Savitri, Wenny; Hutasoit, Masta (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Breast cancer is a disease that can be cured if not found on the stage. More early breast cancer is found, it is very likely that healed getting bigger, but if breast cancer in the late stage found so that it must be operations appointing breast. Post-operative care importance of breast cancer to prevent complications such as infection. The lack of information about post-operative care breast cancer to motivate women to add knowledge about breast area. This information can be obtained through various media both printed and electronics. A person who would have been exposed to more information will be different than not exposed to information. With the lack of information will give an influence on the knowledge one. Objectives: To knew the influence health education in level of knowledge about post-operative care client breast cancer in Daerah Istimewa Yogyakarta. Methods: Design this research is quasi experimental design with One Group Pre test - Post test. Number of sample that is 21 respondents from hospital Panembahan Senopati in Bantul and hospital Wates. Data Analysis is analysis of univariate and analysis of test bivariate using Wilcoxon Signed Rank Test with high significance p<0.05. Results: Client level of knowledge after being given health education most good as many as 14 respondents (66,7%) higher than that before given health education that is most less than 17 respondents (81%). %). Test result Wilcoxon Signed Rank Test, the z value of -4.028 and the p value of 0.000. This shows that the Ï < 0.05 which means health education level of knowledge clients have an influence on post-operative breast cancer. Conclusion: There is influence health education level of knowledge clients in post-operative breast cancer before and after being given health education in Daerah Istimewa Yogyakarta. Keywords: Breast cancer, care, post operative, knowledge